Charge Distribution Controls On‐Target Separation of Low Nucleophilicity Anions in Layered Double Hydroxides (Adv. Mater. Interfaces 31/2022). Issue 31 (3rd November 2022) - Sudare, Tomohito; Tamura, Shuhei; Kashiwazaki, Maru; Nakamura, Yuki; Kawaguchi, Kenta; Shiiba, Hiromasa; Fujisawa, Kazunori; Tipplook, Mongkol; Tanaka, Hideki; Hayashi, Fumitaka; Teshima, Katsuya
Abstract : Nitrate Ion-Separation The underlying prerequisite for materials design to achieve on‐target separation of low nucleophilic nitrate ions has been unclear. By fabricating cation‐ordered layered double hydroxides (LDHs) via topochemical reaction, in article number 2201484, Tomohito Sudare, Katsuya Teshima, and colleagues demonstrate that the hexagonal arrangement effectively facilitates a stable guest–guest interactions–hydrogen‐bond between the interlayer nitrate ions and water molecules, which contributes to efficient nitrate ion‐separation.